FACTORS RELATED TO NURSES' MOTIVATION TO CONTINUE EDUCATION AT THE NATIONAL SPORTS HOSPITAL IN 2024 - Wijaya, Indra; Harahap, Desrinah; Minarningtyas, Asih; Sunirah, Sunirah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Higher education is crucial in developing surgical technology and professional life training. In organizing nursing education, motivation is needed, influencing internal and external factors so that nurses desire to improve their competence. Objective: to find out what factors are related to motivation to continue education nurses at the National Sports Hospital in 2024. This research aimed to determine what factors are related to nurses' motivation to continue their education at the National Sports Hospital in 2024. The type of research used was a cross-sectional design to examine whether there was a relationship between the motivational factors of family support, work environment, income, and nurses' motivation to continue their education. The population of this study consisted of nurses at the National Sports Hospital, totaling 34 respondents, and the sampling technique used was the total sampling technique. The instrument was a questionnaire, and data analysis used univariate and bivariate analysis techniques with the Spearman Rank statistical test. The study's results showed that only the family support variable had a relationship with nurses' motivation to continue their education. In contrast, work environment factors and income did not have a significant relationship: family support (prho = 0.620), work environment (prho = 0.124), and income (prho = 0.199). This research recommends that it is necessary to maximize the role of family support in nurse career development programs in hospitals and increase the role of the work environment and financial support for nurses who will continue their education